Implementasi Integrasi Kurikulum Pengajaran Bahasa Arab di Pondok Modern Darul Ihsan Nganjuk: Analisis Model Integrasi Perspektif Robin Forgaty - Tsalis Riyanto; Badrus; Marita Lailia Rahman; Ervin Yudianto (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2026)
Curriculum is a fundamental component of every educational institution, yet determining an appropriate curriculum remains a significant challenge. Pondok Modern Darul Ihsan Nganjuk addresses this issue by integrating multiple curricula into its educational system. This study examines the institution’s curriculum integration through Robin Fogarty’s framework of curriculum integration models. Using a qualitative approach, the research identifies the integration model applied and evaluates its implications for curriculum implementation. The findings indicate that the Arabic language curriculum primarily reflects the Integrated Model, which connects Arabic instruction with various fields of Islamic studies at the junior and senior secondary levels. In addition, the curriculum incorporates elements of the Nested Model by integrating multiple skills, concepts, and learning standards within individual lessons. These findings demonstrate that the institution adopts a comprehensive curriculum integration approach to enhance the effectiveness of Arabic language learning.